Impact of Dual-Energy Computed Tomography (DECT) Postprocessing Protocols on Detection of Monosodium Urate (MSU) Deposits in Foot Tendons of Cadavers - Klauser, Andrea Sabine; Strobl, Sylvia; Schwabl, Christoph; Kremser, Christian; Klotz, Werner; Vasilevska Nikodinovska, Violeta; Stofferin, Hannes; Scharll, Yannick; Halpern, Ethan (MDPI AG, 2023)
To evaluate two different dual-energy computed tomography (DECT) post-processing protocols for the detection of MSU deposits in foot tendons of cadavers with verification by polarizing light microscopy as the gold standard.
Keywords: dual-energy computed tomography; gout; tendon; foot; monosodium urate deposits